Manpower development: a veritable tool for industrial harmony and societal development (2009)
This paper is a study on the linkages among the terms: manpower development, industrial harmony and societal development. It gives brief synopsis of each and outlines how they can be made to work together to engender industrial harmony and both corporate organizational and national development. The paper concludes that meaningful manpower development would necessarily lead to industrial harmony. This will make room for both corporate organizational and national development resulting in the development the entire society in cyclic manner. It illustrates this conclusion with the results of a study on ten companies to verify how they work together and found that implication of manpower development is meaningful organizational, macro national and the resultant societal development.